2011
DOI: 10.1590/s0100-83582011000100018
|View full text |Cite
|
Sign up to set email alerts
|

Seletividade de herbicidas em mudas das espécies nativas Acacia polyphylla, Enterolobium contortisiliquum (Fabaceae), Ceiba speciosa e Luehea divaricata (Malvaceae)

Abstract: Este trabalho avaliou a seletividade de herbicidas sobre espécies nativas de florestas estacionais semideciduais de São Paulo, amplamente utilizadas em projetos de restauração de ecossistemas naturais degradados: Acacia polyphylla e Enterolobium contortisiliquum (Fabaceae), e Ceiba speciosa e Luehea divaricata (Malvaceae). Os tratamentos consistiram de uma testemunha sem herbicida e da aplicação de herbicidas imazapyr (125, 250, 500, 1.000, 2.000 e 3.000 g ha-1), sulfentrazone (100, 200, 400, 800, 1.400 e 2.40… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 26 publications
2
16
0
3
Order By: Relevance
“…A redução na produção de massa seca da parte aérea também foi observada para diferentes doses de imazapyr, sulfentrazone e glyphosate em mudas de Acacia polyphylla, indicando suscetibilidade da espécie aos produtos aplicados. O metribuzin foi seletivo para a A. polyphylla, porque não causou redução na produção de massa seca da parte aérea da planta (MONQUERO et al, 2011).…”
Section: Resultsunclassified
“…A redução na produção de massa seca da parte aérea também foi observada para diferentes doses de imazapyr, sulfentrazone e glyphosate em mudas de Acacia polyphylla, indicando suscetibilidade da espécie aos produtos aplicados. O metribuzin foi seletivo para a A. polyphylla, porque não causou redução na produção de massa seca da parte aérea da planta (MONQUERO et al, 2011).…”
Section: Resultsunclassified
“…Christoffoleti et al (1998) observed that imazapyr is completely selective for Pinus spp., that tolerates applications before and after transplanting, whose doses provide longer residual weed control. Monquero et al (2011) also verified that this herbicide was selective in Ceiba speciosa seedlings and Luehea divaricata, however, in its higher level, it caused phytotoxicity with necrosis and deformation of leaves and shoots but did not inhibit the plant development.…”
Section: Resultsmentioning
confidence: 63%
“…According to Brancalion et al (2009), this very same effect occurred with the setoxidim herbicide in seedlings of Senna multijuga and Guazuma ulmifolia Lam. Monquero et al (2011) also verified that the leaves of Kielmeyera lathrophyton were damaged but gradually recovered as they grew older. From 21 DAA, the seedlings showed more intense toxicity symptoms as the herbicide level was doubled.…”
Section: Resultsmentioning
confidence: 67%
See 1 more Smart Citation
“…In order to counteract infesting weeds, it is common to use herbicides that block the germination of seeds or the establishment of weed seedlings [2].…”
Section: Introductionmentioning
confidence: 99%